2007
DOI: 10.1007/s12011-007-8051-1
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Trace Elements from Biological Tissue by Formalin Fixation

Abstract: In studies of trace elements in biological tissue, it is imperative that sample handling does not substantially change element concentrations. In many cases, fresh tissue is not available for study, but formalin-fixed tissue is. Formalin fixation has the potential to leach elements from the tissue, but few studies have been published in this area. The concentrations of 19 elements were determined by high-resolution inductively coupled plasma mass spectrometry in formalin in which human and rat brain samples ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
60
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 10 publications
11
60
1
Order By: Relevance
“…It has been reported that formalin leaches out iron from the brain and other tissues in a time-dependent manner (Smith et al, 1997). An experimental approach using atomic absorption spectroscopy revealed that a formalin fixation lasting 4 years leads to an average brain iron reduction of 43% (Schrag et al, 2010), although some studies have suggested a smaller effects (Chuaanusorn et al, 1997;Gellein et al, 2008). At the time of imaging, the brain of Case MS-1 had been stored in formalin for 3 years, compared with 3 months for Case MS-2 and 2 months for the non-multiple sclerosis donor.…”
Section: Subpial Iron Accumulation Was Present In Case Ms-1mentioning
confidence: 99%
“…It has been reported that formalin leaches out iron from the brain and other tissues in a time-dependent manner (Smith et al, 1997). An experimental approach using atomic absorption spectroscopy revealed that a formalin fixation lasting 4 years leads to an average brain iron reduction of 43% (Schrag et al, 2010), although some studies have suggested a smaller effects (Chuaanusorn et al, 1997;Gellein et al, 2008). At the time of imaging, the brain of Case MS-1 had been stored in formalin for 3 years, compared with 3 months for Case MS-2 and 2 months for the non-multiple sclerosis donor.…”
Section: Subpial Iron Accumulation Was Present In Case Ms-1mentioning
confidence: 99%
“…The degree of leaching is time dependent and very different for different elements. A study ( 37 ) that used highspatial-resolution inductively coupled plasma mass spectrometry to measure 19 metal elements in the human brain showed that there was moderate iron leaching after long-term storage (about 20 years), compared with other metal showed that in this area (high iron, normal myelin), both phase and R2* had a prominent contrast (high R2* values and negative frequency shift). However, in the inner part of the lesion, where iron and myelin were both preserved, an increased R2* but little frequency shift was observed.…”
Section: Neuroradiology: High-field-strength Mr Imaging Of Chronic Mumentioning
confidence: 99%
“…The lower iron content in the Perl stain of the PD sample found here may be due to the fixation time being longer for the PD sample compared to the HC samples (z2 vs 1 year). 21,22 The mismatch between the hypointensity observed on the T2*-weighted MRI and Perl stains is interesting. Since the Perl stain is sensitive only to iron (III), this could be due to higher iron (II) content in PD brains, which could relate to the fixation process, but would also be consistent with increased oxidative stress due to ferrous iron in PD.…”
mentioning
confidence: 99%
“…Third, the low iron content in the Perl stain of the PD sample was paradoxical and indicates that future studies should use PM samples with similar fixation times. 21,22,31 Finally, it was difficult to distinguish between the SNpc and VTA, as both contain dopaminergic, neuromelanin-pigmented cells, but they can be separated based on the anatomical location, cell density (which is lower in VTA), or using the issuing fibers of the third cranial nerve as landmarks for VTA. This study identifies the substructure of the SNpc that is visible on 7 T T2*-weighted images 12 as nigrosome 1.…”
mentioning
confidence: 99%